Treason : a novel - Gingrich, Newt; Earley, Pete (Center Street, 2016)
"Leading politician and bestselling author Newt Gingrich and novelist Pete Earley are back with the gripping sequel to Duplicity. Islamic terrorism is growing on American soil, and in Newt Gingrich's new novel, TREASON, an attempted assassination at the highest level points to treason at the highest corridors of power. Captain Brooke Grant, Sergeant Walks Many Miles, and Representative Thomas "The Chairman" Stanton have been hunting down Islamic terrorist mastermind, The Falcon, and he has now marked them for death. His terrorists in place in America are training to execute his revenge--and they are happy to die for their cause. TREASON will leave readers on the edge of their seats as The Falcon continues to terrorize the U.S"--